SEJARAH PERS ISLAM DI PALEMBANG (1965-1972): Studi atas Surat Kabar Mingguan “Nusa Putera” - Ottoman M.Hum (Fakultas Adab dan Humaniora UIN Raden Fatah, 2016)
The press is an institution of mass communication that could serve the interests of the information society. Everyday the press provides an overview of a variety of events, providing a place for the community to issue a written opinion and pass on societal values from generation to generation. In the face of changes take place rapidly in communities clearly such information is very helpful. Weekly Newspaper